Mechanotransduction Regulates the Interplays Between Alveolar Epithelial and Vascular Endothelial Cells in Lung - Lin, Chuyang; Zheng, Xiaolan; Lin, Sha; Zhang, Yue; Wu, Jinlin; Li, Yifei (Frontiers in Physiology, 2022)
Mechanical stress plays a critical role among development, functional maturation and pathogenesis of pulmonary tissues, especially for the alveolar epithelial cells and vascular endothelial cells located in the microenvironment established with vascular network and bronchial-alveolar network. Alveolar epithelial cells are mainly loaded by cyclic strain and air pressure tension. While vascular endothelial cells are exposed to shear stress and cyclic strain. Currently, the emerging evidences demonstrated that non-physiological mechanical forces would lead to several pulmonary diseases, including pulmonary hypertension, fibrosis, and ventilation induced lung injury. Furthermore, a series of intracellular signaling had been identified to be involved in mechanotransduction and participated in regulating the physiological homeostasis and pathophysiological process. Besides, the communications between alveolar epithelium and vascular endothelium under non-physiological stress contribute to the remodeling of the pulmonary micro-environment in collaboration, including hypoxia induced injuries, endothelial permeability impairment, extracellular matrix stiffness elevation, metabolic alternation and inflammation activation. In this review, we aim to summarize the current understandings of mechanotransduction on the relation between mechanical forces acting on the lung and biological response in mechanical overloading related diseases. We also would like to emphasize the interplays between alveolar epithelium and vascular endothelium, providing new insights into pulmonary diseases pathogenesis, and potential targets for therapy.